Mechanical Property Improvement for Aluminum Alloy Al-7Si with Additive Material of Al-TiB and Heat Treatment of T5 - Suhariyanto Suhariyanto; Syamsul Hadi; Mahirul Mursid; Gatot Dwi W (Institut Teknologi Sepuluh Nopember, 2019)
Aluminum alloy Al-7Si is suitable for material of wheel rim of racing car, however its mechanical properties has not met the required standard JIS H5202, so it needs to be improved. Improving mechanical properties can be done by adding element alloys and heat treatment. This present research in concerning with Al-TiB enhancement into the Al-7Si aluminum alloy to increase the Titanium content of 0.13%w to 0.14%w, 0.15%w, 0.16%w until 0.21%w. Therefore, these samples were treated by heat treatment T5. The Addition of Al-TiB caused the micro structure of the grain become smaller and softer, and also increases the mechanical properties (UTS and Hardness), but it has not met standard JIS H5202 yet. After heat treatment T5, the form of grain change from ellipse to circular, the mechanical properties improve significantly and beyond the standard JIS H5202.